Economic Analysis of Queuing Model with Reverse Balking and Retention of Impatient Customers (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Natasha, Dr. Deepak Gupta, Dr. Sapana SharmaThe idea of reverse balking with reneging and retention in a queuing system for multiple servers is developed in this work. It focuses on the behaviour of new customers who are highly likely to join it, and vice versa. Customers may become impatient after logging in and quit the system, thus the idea of retention is used to persuade them to wait in line. Here, the defined system's steady state solution is found, and then several efficacy tests are run. The model is subjected to comparison and numerical analysis. Additionally, a few models’ exceptional instances are examined.